Out of Asia: Biogeography of fungal populations reveals Asian origin of diversification of the Laccaria amethystina complex, and two new species of violet Laccaria. Issue 11 (November 2017) - Vincenot, Lucie; Popa, Flavius; Laso, Francisco; Donges, Kathrin; Rexer, Karl-Heinz; Kost, Gerhard; Yang, Zhu L.; Nara, Kazuhide; Selosse, Marc-André
Abstract: Purple Laccaria are ectomycorrhizal basidiomycetes associated with temperate forests all over the Northern Hemisphere in at least two taxa: Laccaria amethysteo-occidentalis in North America, and L. amethystina complex in Eurasia, as shown by Vincenot et al. (2012). Here, we combine a further study of the genetic structure of L. amethystina populations from Europe to southwestern China and Japan, using neutral Single Sequence Repeat (SSR; microsatellite) markers; and a systematic description of two novel Asian species, namely Laccaria moshuijun and Laccaria japonica, based on ecological, morphological, and molecular criteria (rDNA sequences). Population genetics provides evidence of the ancient isolation of three regional groups, with strong signal for speciation, and suggests a centre of origin of modern populations closest to present-day Chinese populations. Phylogenetic analyses confirm speciation at the molecular level, reflected in morphological features: L. moshuijun samples (from Yunnan, China) display strongly variable cheilocystidia, while L. japonica samples (from Japan) present distinctive globose to subglobose spores and clavate cheilocystidia. This study of a species complex primarily described with an extremely wide ecological and geographical range sheds new light on the biodiversity and biogeography of ectomycorrhizal fungi. Highlights: Ectomycorrhizal Laccaria amethystina covers a wide and contrasted distribution area. Neutral molecular markers reveal at least three regional genetic pools over Eurasia. Metapopulations genetic structure suggest a geographic origin close to present China. Phylogenetics, ecology, micro- and macro-morphology indicate a species' complex. Two novel species are described: Laccaria moshuijun from China and Laccaria japonica from Japan.